PERAN BIROKRAT GARDA TERDEPAN DALAM IMPLEMENTASI KEBIJAKAN - Saepudin, Eli Apud; Zulfikar, Meiby; Suryasuciramdhan, Arfian; Endayani, Endayani; Arifin, Suherman (Gapenas Publisher, 2023)
Frontline bureaucrats, often called street-level bureaucrats, play a crucial role in ensuring the successful implementation of public policies. They interact directly with the public in delivering public services and running government programmes. Therefore, understanding their role is crucial to realising effective, efficient and accountable policies. The research method used is descriptive qualitative by collecting data from various sources and then analysing it. Research Objectives to determine Public Service Delivery, Implementation of Government Programmes, Interaction with the Community, Policy Evaluation, Agent of Change. Understanding the roles and challenges of frontline bureaucrats, as well as efforts to improve their roles, is essential to realising good governance and public policies that benefit the community